Pregnancy and neonatal outcomes following time-lapse versus conventional embryo culture: a retrospective cohort study - Li, Wei; Xin, Miaomiao; Xue, Xia; He, Tingting; Shi, Juanzi (Frontiers in Endocrinology, 2026)
ObjectiveTo compare pregnancy and neonatal outcomes between time-lapse and conventional embryo culture in frozen embryo transfer (FET) cycles.DesignRetrospective cohort study.SettingTertiary-care academic medical center.PatientsThis retrospective cohort study included 15,697 women who underwent single blastocyst transfer during their first FET cycle from January 2017 to December 2023.Intervention(s)None.Main Outcome Measure(s)The pregnancy outcomes and the neonatal outcomes.Result(s)Our study demonstrated that pregnancy outcomes were comparable between the time-lapse embryo culture group and the conventional embryo culture group, including biochemical pregnancy (relative risk [RR] = 1.02; 95% confidence interval [CI], 0.92–1.13), clinical pregnancy (RR = 1.07; 95% CI: 0.96–1.18), ectopic pregnancy (RR = 0.65; 95% CI: 0.37–1.17), miscarriage (RR = 0.99; 95% CI: 0.86–1.16), live birth (RR = 1.07; 95% CI: 0.98–1.18) and multiple live births (RR = 0.94; 95% CI: 0.57–1.54). Additionally, no statistically significant differences were observed in neonatal outcomes, including cesarean delivery, male gender, very preterm birth, preterm birth, very low birth weight, low birth weight) or high birth weight. Similarly, there were no statistically significant differences in either gestational age or birth weight between the two groups.Conclusion(s)Our study demonstrated that time-lapse embryo culture yields comparable pregnancy and neonatal outcomes to conventional embryo culture, suggesting that this technology is both effective and safe for embryo incubation.